Simulation games as tools for integrative dynamic learning: The case of the management course at the University of Algarve - Kikot, Tatiana (2014)
Today, in order to people or organizations survive in a changing environment it is essential to adapt. Learning provided to people is a key feature for an active response since it implies acquiring knowledge, skills and competencies to cope successfully with different circumstances. Literature has focused on how digital games support education because simulators represent dynamic models of real situations; so, their goal is to ensure that the player denotes his decisions consequences. When teaching certain skills through these games, a reflection stage is crucial to evaluate the experiences gathered during the simulation and promote knowledge appliance by participants into the real world. Due to its multiple scientific contributions, gaming can overlap a valid solution to prepare learners understanding regarding complex contexts. This research denotes an ongoing PhD research about the characteristics of a management course unit (at the University of Algarve, Portugal) that explores a business simulator- Cesim Global Challenge- for learning purposes, as well as the effectiveness of an integrative approach (new learning environments) on students’ engagement and dynamic learning outcomes. From the earlier empirical data is understandable game-based learning advantages and disadvantages within Management and Entrepreneurship courses.